Regulatory mechanisms of macrophage polarization in adipose tissue - Pan, Dun; Li, Guo; Jiang, Chunlin; Hu, Jinfeng; Hu, Xiangming (Frontiers in Immunology, 2023)
In adipose tissue, macrophages are the most abundant immune cells with high heterogeneity and plasticity. Depending on environmental cues and molecular mediators, adipose tissue macrophages (ATMs) can be polarized into pro- or anti-inflammatory cells. In the state of obesity, ATMs switch from the M2 polarized state to the M1 state, which contributes to chronic inflammation, thereby promoting the pathogenic progression of obesity and other metabolic diseases. Recent studies show that multiple ATM subpopulations cluster separately from the M1 or M2 polarized state. Various factors are related to ATMs polarization, including cytokines, hormones, metabolites and transcription factors. Here, we discuss our current understanding of the potential regulatory mechanisms underlying ATMs polarization induced by autocrine and paracrine factors. A better understanding of how ATMs polarize may provide new therapeutic strategies for obesity-related diseases.